Analysis of SMKK Costs in the Ngantang Sub-District Office Renovation Project Based on Minister of PUPR Regulation No. 10 of 2021 - Lakshita Umanis Fauzi; Tri Kuncoro; Mei Fajri Anugrah Sukma; Retno Dwi (CV. Ulil Albab Corp, 2026)
This study aims to evaluate the appropriateness of the Construction Safety Management System (SMKK) cost allocation in the Ngantang Sub-District Office Renovation Project, Malang Regency, against the provisions of Minister of PUPR Regulation No. 10 of 2021. The research method used is descriptive quantitative with a desk study approach to analyze the Engineer's Estimate (EE) documents of the project valued at IDR 199.732.000.00. Risk analysis results indicate the presence of